About the displacement of things y gente talk shared by Paulo Nazareth at the cycle of readings on august 25, 2022 - Nazareth, Paulo (2023)
In September 2022, Paulo Nazareth participated in the Cycle of Readings of the Extension Project Embodyment poetics in pandemic landscapes: creating communities to revive affections with the city, held remotely by the Institute of Arts of the State University of Campinas. This text is a transcription of the homonymous speech of this Brazilian artist, which took place in a performative way, constituting itself, in itself, as an artistic creation.